Mechanism and Therapeutic Progress of One-Carbon Metabolic Key Enzyme: Serine Hydroxymethyltransferase 2 in Cancer - Siqiang Zhu; Yuan Liu; Hao Chen; Xingyu Zhu; Xinyu Liu; Kang Xu; Yaodong Sang; Liang Shang; Wei Chong; Leping Li (Clinical Medicine Insights: Oncology)
Serine hydroxymethyltransferase 2 (SHMT2) is a crucial mitochondrial enzyme in 1-carbon (1C) metabolism. It catalyzes the conversion of serine to glycine, generating 1C units essential for purine and pyrimidine synthesis, thereby supporting DNA replication and repair. Abnormally high expression is associated with malignant progression and treatment tolerance in various cancers. This review systematically summarizes the functions of SHMT2 in different types of cancer, underscoring on its roles in metabolism, immune microenvironment, and key signaling pathways (PI3K/AKT/mTOR, JAK-STAT, etc.) and outlines its epigenetic regulation and posttranslational modification mechanisms. Compared with the existing research, we focused on the latest regulatory mechanisms of SHMT2 and its potential in cancer treatment, such as the development and application of small-molecule inhibitors (SHIN2 and AGF347).